Interfacial water at the trialanine hydrophilic surface: a DFT electronic structure and bottom-up investigation12. Issue 26 (14th July 2015) - Lanza, Giuseppe; Chiacchio, Maria Assunta
<x xml:space="preserve">Abstract</x> A model describing a network of hydrogen bonded water-trialanine has been developed to estimate hydration effects on various conformers of the peptide.